The influence of upper-body pre-cooling on repeated sprint performance in moderate ambient temperatures - Cheung, S. S.; Robinson, A. M. (Journal of Sports Sciences, 2004)
In this study, we examined the effects of upper-body pre-cooling before intermittent sprinting exercise in a moderate environment. Seven male and three female trained cyclists (age 26.8+/-5.5 years, body mass 68.5+/-9.5 kg, height 1.76+/-0.13 m, V O(2peak) 59.0+/-11.4 mL. kg(-1). min(-1); mean+/-s) performed 30 min of cycling at 50% V O(2peak) interspersed with a 10-s Wingate cycling sprint test at 5 min intervals. The exercise was performed in a room controlled at 22(o)C and 40% relative humidity. In the control session, the participants rested for 30 min before exercise. In the pre-cooling session, the participants wore the upper segment of a liquid conditioning garment circulating 5(o)C coolant until rectal temperature decreased by 0.5(o)C. Rectal temperature at the start of exercise was significantly lower in the pre-cooling (36.5+/-0.3(o)C) than in the control condition (37.0+/-0.5(o)C), but this difference was reduced to a non-significant 0.4(o)C throughout exercise. Mean skin temperature was significantly lower in the pre-cooling (30.7+/-2.3(o)C) than in the control condition (32.5+/-1.6(o)C) throughout exercise. Heart rate during submaximal exercise was similar between the two conditions, although peak heart rate after the Wingate sprints was significantly lower in the pre-cooling condition. With pre-cooling, mean peak power (909+/-161 W) and mean overall power output (797+/-154 W) were similar to those in the control condition (peak 921+/-163 W, mean 806+/-156 W), with no differences in the subjective ratings of perceived exertion. These results suggest that upper-body pre-cooling does not provide any benefit to intermittent sprinting exercise in a moderate environment.